Comparative Oil Composition Study of the Endemic Moroccan Olive (Olea europaea subsp. maroccana) and Wild Olive (var. Sylvestris) in Central West Morocco. (2nd February 2021) - Elgadi, Sara; Ouhammou, Ahmed; Zine, Hamza; Maata, Nadia; Ait Babahmad, Rachid; El Antari, Abderraouf
Abstract : Six wild olive subspecies ( Olea europaea L.) are currently recognised globally, with two taxa cooccurring in the argan tree area in Central West Morocco: the widespread Mediterranean subspecies europaea var. Sylvestris (the so-called oleaster) and the microendemic subspecies maroccana . Despite its taxonomic and ecological importance, the chemical composition of subsp. maroccana oil remains poorly known. Therefore, the aim of this study is to investigate the oil content and the chemical composition of subsp. maroccana and var. Sylvestris as well as comparing their proprieties during two consecutive years (2017 and 2018) from the same geographical area. The fatty acid and the sterol compositions were analysed using gas chromatography. Additionally, the tocopherol content was determined using high-performance liquid chromatography. The total amount of unsaturated fatty acids was higher in maroccana (85.24%) than that in oleasters (79.05%). Additionally, the tocopherol and phytosterol content of the maroccana oil (1232.35 mg/kg and 312.75 mg/100 g, resp.) was approximately twofold higher than in oleasters (661.35 mg/kg and 210.06 mg/100 g, resp.). Analysis of variance and principal component analysis (PCA) of the chemical composition highlighted a significant difference between the quantitative and qualitative properties of their oil. Finally, these findings suggest that maroccana oil could be considered as a potential source of vitamin E, essential fatty acids, and sterols and can provide a nutraceutical oil for the local population. While this work contributes to the study of olive tree biodiversity, further investigations are still necessary to guide the putative nutraceutical use of subspecies maroccana .